2021
DOI: 10.1111/ppa.13387
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bemisia tabaci Mediterranean cryptic species on soybean in São Paulo and Paraná States (Brazil) and interaction of cowpea mild mottle virus with whiteflies

Abstract: Since the detection of Bemisia tabaci Middle East-Asia Minor 1 (MEAM1) species in Brazil in the early 1990s, this whitefly has been the predominant species and the main viral vector in the country. In this work, whiteflies were collected from commercial soybean fields near and far from greenhouses where Mediterranean (MED) species had previously been detected infesting vegetable crops. Results indicated that MEAM1 was the predominant whitefly species in soybean in most sampling sites, while MED was found colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
(117 reference statements)
1
5
0
Order By: Relevance
“…This study also revealed that MED has already adapted to the open‐field cultivated crops in Santa Catarina and was probably being introduced with the domestic trading of ornamental plants because MED was first reported in an ornamental crop in Lages, Santa Catarina State (Moraes et al., 2018). MED is still adapting to Brazilian crops and has only been reported in cultivated crops in São Paulo and Paraná states as well as in the Federal District of Brasília (Bello et al., 2020a; Bello et al., 2021; Rodrigues et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also revealed that MED has already adapted to the open‐field cultivated crops in Santa Catarina and was probably being introduced with the domestic trading of ornamental plants because MED was first reported in an ornamental crop in Lages, Santa Catarina State (Moraes et al., 2018). MED is still adapting to Brazilian crops and has only been reported in cultivated crops in São Paulo and Paraná states as well as in the Federal District of Brasília (Bello et al., 2020a; Bello et al., 2021; Rodrigues et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the introduction of this whitefly species into the state of São Paulo was reported, and it was linked to infestations in ornamental plants (Moraes et al, 2017(Moraes et al, , 2018. This whitefly spread to different states targeting ornamental plants, but infestation of cultivated crops was only reported in São Paulo, Paraná and the Federal District of Brasilia (Bello et al, 2020a;Bello et al, 2021;Rodrigues et al, 2021).…”
mentioning
confidence: 99%
“…In Brazil, MED spread across the southern region (Moraes et al, 2017), mainly on ornamentals and vegetables. MED was also reported in open fields on tomatoes (Bello et al, 2020) and soybean fields (Bello et al, 2021) in the Southern region, both events associated with population outbreaks and transmission of plant viruses. However, our results suggest that MED has not been established on open field crops in Brazil's Central and North regions.…”
Section: Discussionmentioning
confidence: 88%
“…In unstressed leaves, it was observed that the application of vermicompost HA promoted an increase in the genera Rickettsia, Candidatus hamiltonella, and Candidatus portiera (Figure 4), recognized endosymbionts of whitefly, a pest that causes damage to soybean plants (Bello et al, 2021). Despite the presence of these taxa, the prevalence of these groups was not observed in all replicates, possibly being a punctual contamination of one of the biological replicates.…”
Section: Resultsmentioning
confidence: 99%